Media Management of Tiktok @Jogjaskena Account as Information Media for Yogyakarta Community Music Concert in 2023 - Muhammad Abid As-shobir; Krisna Mulawarman (Jogjakarta Communication Conference (JCC), 2024)
The @jogjaskena account serves as a platform for sharing entertainment activities, particularly music concerts in Yogyakarta. This research is prompted by the significant reliance of social media users on @jogjaskena for concert information, prompting an examination of its media management. The study aims to analyze how media management operates on the @jogjaskena TikTok account, specifically targeting the awareness of Yogyakarta's residents regarding music events. Employing the POAC theory, encompassing planning, organizing, directing, and supervising media management, the research adopts a qualitative approach with a case study focus. Data collection involves interviews and documentation, followed by analysis stages of data reduction, presentation, and conclusion. Findings reveal @jogjaskena's utilization of media management strategies, including selecting engaging content, leveraging TikTok's creative features, engaging with followers, and collaborating with local music scene stakeholders. Moreover, active monitoring and evaluation of content performance enhance the account's quality. These findings highlight the importance of effective media management in utilizing TikTok for music concert information dissemination, showcasing @jogjaskena's success in enhancing Yogyakarta residents' awareness of music events and establishing itself as a vital information source.